2018
DOI: 10.3892/ol.2018.8142
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of suppressor of fused in regulating the hedgehog signalling pathway (Review)

Abstract: Highly conserved throughout evolution, the hedgehog (Hh) signalling pathway has been demonstrated to be involved in embryonic development, stem cell maintenance and tissue homeostasis in animals ranging from invertebrates to vertebrates. In the human body, a variety of cancer types are associated with the aberrantly activated Hh signalling pathway. Multiple studies have revealed suppressor of fused (Sufu) as a key negative regulator of this signalling pathway. In vertebrates, Sufu primarily functions as a tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 108 publications
4
24
0
Order By: Relevance
“…However, the precise underlying molecular mechanisms need further investigation. SUFU, a key negative regulator of the Hedgehog pathway, can bind to Gli to inhibit the Hedgehog pathway activity [15], while SUFU protein can be degraded by the CRL Fbxl17 E3 ubiquitin ligase [16]. In the current study, we demonstrated that SUFU accumulation inactivated the Hedgehog signaling upon ROC1 knockdown, while blockage of SUFU expression restored the Hedgehog signaling suppression triggered by the ROC1 knockdown, indicating that ROC1-regulated the Hedgehog signaling in bladder cancer was dependent on SUFU degradation.…”
Section: Dysregulation Of Cell Proliferation Is a Landmark During Tumsupporting
confidence: 48%
See 1 more Smart Citation
“…However, the precise underlying molecular mechanisms need further investigation. SUFU, a key negative regulator of the Hedgehog pathway, can bind to Gli to inhibit the Hedgehog pathway activity [15], while SUFU protein can be degraded by the CRL Fbxl17 E3 ubiquitin ligase [16]. In the current study, we demonstrated that SUFU accumulation inactivated the Hedgehog signaling upon ROC1 knockdown, while blockage of SUFU expression restored the Hedgehog signaling suppression triggered by the ROC1 knockdown, indicating that ROC1-regulated the Hedgehog signaling in bladder cancer was dependent on SUFU degradation.…”
Section: Dysregulation Of Cell Proliferation Is a Landmark During Tumsupporting
confidence: 48%
“…To explore the molecules that were primarily responsible for Hedgehog activation, we assessed SUFU expression in ROC1-knockdown or overexpression bladder cancer cells. SUFU protein act as a CRL substrate and the naturally occurring Hedgehog inhibitor [15,16]. Our data showed that expression of SUFU protein was signi cantly elevated in the ROC1-knockdown 5637 cancer cells compared with that of the control cells (Fig.…”
Section: Roc1 Activation Of Hedgehog Signaling Through Sufu (Suppressmentioning
confidence: 62%
“…Full length GLI2 and GLI3 are free to translocate to the nucleus as transcriptional activators, while SUFU is degraded. A key function of SUFU is also preserving a pool of full length GLI2/3 proteins by preventing complete degradation mediated by SPOP, and as soon as HH-GLI signaling is activated these proteins are derepressed and readily activate target gene transcription [ 42 , 43 ]. In addition to the cytoplasm, SUFU also regulates GLI proteins in the nucleus, where it is able to recruit specific co-repressor complexes, such as SAP18-mSin3-HDAC and p66β and thereby suppress GLI transcription activity [ 44 , 45 , 46 ].…”
Section: The Hh-gli Signaling Pathwaymentioning
confidence: 99%
“…Basal cell carcinomas (BCCs) arise from aberrant activation of the hedgehog (Hh) signaling pathway, a highly conserved evolutionary pathway crucial for the differentiation of embryonic structures such as the central nervous, integumentary and musculoskeletal systems 1 2. Within this pathway, Hh ligands bind to tumour suppressor PTCH1, relieving PTCH1’s inhibitory effect on the protein, smoothened (SMO) 3. Active SMO promotes the dissociation of glioma-associated oncogene homologues (GLIs) from SUFU (Suppressor of Fused), a tumour suppressor and negative regulator of the Hh pathway.…”
Section: Introductionmentioning
confidence: 99%